Beneficial effects of vitamin E supplementation against the oxidative stress on Cylindrospermopsin-exposed tilapia (Oreochromis niloticus). (15th September 2015) - Guzmán-Guillén, Remedios; Prieto Ortega, Ana I.; Martín-Caméan, Ana; Cameán, Ana M.
Abstract: Cylindrospermopsin (CYN) is known to produce changes in some oxidative stress biomarkers in fish acutely and subchronically exposed to the toxin. The present study investigated the effects of vitamin E supplementation against the oxidative stress induced by pure CYN in tilapia ( Oreochromis niloticus ). Fish were pretreated with 700 mg vitamin E/kg fish body weight (bw)/day for 7 days by oral route, and on day seven, they received a single oral dose of 400 μg pure CYN/kg fish bw, and were killed after 24 h. The biomarkers evaluated included lipid peroxidation (LPO), protein and DNA oxidation, glutathione-S-transferase (GST), glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT) and γ-glutamyl-cysteine synthetase (γ-GCS) activities, and ratio of reduced glutathione-oxidized glutathione (GSH/GSSG). This is the first study showing that vitamin E supplementation is effective at reducing the toxicity induced by CYN, recovering the biomarkers assayed to basal levels. Therefore, vitamin E can be considered a useful chemoprotectant that reduces hepatic and renal oxidative stress and can be used in the prophylaxis and treatment of CYN-related intoxication in fish. Highlights: Vitamin E supplementation restores oxidative stress biomarkers to control levels in CYN-intoxicated fish (liver and kidney). This effect is mainly observed in the liver of intoxicated fish. Vitamin E supplementation did not affect any biomarker values in fish not exposed to CYN, representing a safe compound. Vitamin E can be used as chemoprotectant in the prophylaxis of CYN-intoxications in fish.